2003
DOI: 10.1029/2002ja009696
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical response of the magnetosphere‐ionosphere system to a solar wind dynamic pressure oscillation

Abstract: [1] On 28 February 1998, four quasi-periodic pressure pulses with an amplitude of a few nPa detected by ACE gave rise to periodic compressions of the magnetosphere with period of about 14 min. In concert with periodic compressed and expanded states of the magnetosphere forced directly by the pressure variation, a coherent geomagnetic field fluctuation with the same period appeared on a global scale and was recorded at stations located from polar to equatorial regions. Most ground-level geomagnetic field signat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 43 publications
7
63
2
Order By: Relevance
“…Fujita et al [] suggested in their simulation study that the convection pattern in the ionosphere in their second main impulse phase is directly connected to the Region 2 current in the case of the negative impulse. A connection between the magnetosphere and the ionosphere by FACs was discussed by Motoba et al [] and Fujita et al []. From our simulation results, we find two major vortices in the plasma sheet, one in the dawn and the other in the dusk, each with a different rotation sense (counterclockwise in the dawn and clockwise in the dusk when viewed from the north).…”
Section: Summary and Discussionsupporting
confidence: 65%
“…Fujita et al [] suggested in their simulation study that the convection pattern in the ionosphere in their second main impulse phase is directly connected to the Region 2 current in the case of the negative impulse. A connection between the magnetosphere and the ionosphere by FACs was discussed by Motoba et al [] and Fujita et al []. From our simulation results, we find two major vortices in the plasma sheet, one in the dawn and the other in the dusk, each with a different rotation sense (counterclockwise in the dawn and clockwise in the dusk when viewed from the north).…”
Section: Summary and Discussionsupporting
confidence: 65%
“…The excellent agreement in V i and ∆ H (Figure e) indicates that the magnetic perturbations are also caused by the corresponding perturbations in the IMF. Therefore, magnetic perturbations at a single station can be used to represent the perturbations caused by the IMF/solar wind, as done in many previous studies (e.g., Kikuchi et al, , ; Motoba et al, ; Nishida, , ).…”
Section: Observationsmentioning
confidence: 99%
“…Motoba et al . [] also believed that the ionospheric convection associated with the MI signature is closely coupled with the magnetospheric convection. By simulation, Slinker et al .…”
Section: Introductionmentioning
confidence: 99%